Посилення інституційної спроможності Рад з питань внутрішньо переміщених осіб через організаційно-правові зміни - Петров, В. В.; Petrov, V. (ЦНТУ, 2025)
Мета статті - на основі аналізу організаційно-правового механізму та особливостей діяльності, розробити пропозиції щодо посилення інституційної спроможності Рад з питань ВПО тощо. The aim of the article - based on the analysis of the organizational and legal mechanism and peculiarities of activity, to develop proposals for strengthening the institutional capacity of IDP Councils etc.
Strengthening the Institutional Capacity of Councils on Internally Displaced Persons through Organizational and Legal Changes
Keywords: управління; внутрішньо переміщені особи (ВПО); інституційна спроможність; Ради з питань ВПО; management; internally displaced persons (IDPs); institutional capacity; IDP Councils